Developing Bilingual Informative Articles for PT Metro Mesin Mendunia’s Website - Aisyah Kamila El Savira; Hiqma Nur Agustina (Jurnal Lingua Idea, 2026)
PT Metro Mesin Mendunia is a manufacturing company that produces advanced industrial machines for various sectors, such as the food and beverage sector, agriculture, and construction. While aiming for overseas expansion, the company lacked English-language resources. To address this issue while maintaining its domestic market presence, this study developed bilingual informative articles in English and Indonesian for the company’s website. This research employed the five-stage Design and Development Research (DDR) method developed by Richey and Klein. Data were collected through interviews, observations, and structured questionnaires. Throughout the analysis, design, and development stages, the researcher established a practical guideline for content creation. This guideline emphasized clear technical explanations, communicative translation, and engaging multimedia layouts. The developed articles were then validated by a language expert and a product content expert. During the implementation and evaluation stages, field testing was conducted with 35 diverse respondents. The results indicated that the articles were highly effective, achieving an impressive average score of 4.59 out of 5. This positive outcome was primarily due to the understandable language, clear visual representations, and coherent layout of the content. In conclusion, this study offers practical guidelines for creating digital bilingual content in the manufacturing sector. The resulting articles serve as an effective promotional tool to improve product accessibility and communication for both domestic and international audiences.